Synthesis and characterization of novel 7-oxy-3-ethyl-6-hexyl-4-methylcoumarin substituted metallo phthalocyanines and investigation of their photophysical and photochemical properties - YALÇIN, BAHATTİN; ÖZDEMİR, MÜCAHİT; SALAN, ÜMİT (ROYAL SOC CHEMISTRY, 2019)
In this study, the synthesis of novel 7-hydroxy-3-ethyl-6-hexyl-4-methylcoumarin (1), four respective phthalonitriles; 4-(7-oxy-3-ethyl-6-hexyl-4-methylcoumarin)phthalonitrile (2), 3-(7-oxy-3-ethyl-6-hexyl-4-methylcoumarin)phthalonitrile (3), 4-chloro-5-(7-oxy-3-ethyl-6-hexyl-4-methylcoumarin)phthalonitrile (4), and 4,5-bis(7-oxy-3-ethyl-6-hexyl-4-methylcoumarin)phthalonitrile (5) and their corresponding alpha tetra, beta tetra and beta octa 7-oxy-3-ethyl-6-hexyl-4-methylcoumarin and beta octa 4-chloro-5-(7-oxy-3-ethyl-6-hexyl-4-methylcoumarin) substituted Zn(ii) (6a-9a) and In(iii) Cl (6b-9b) phthalocyanines has been performed. The novel purified compounds were characterized by standard characterization techniques such as elemental analysis, thermal analysis, FT-IR, UV-vis, H-1-NMR and MALDI-TOF mass spectrometry. All of the obtained phthalocyanines showed lipophilic behaviour with excellent solubility in organic solvents such as acetone, dichloromethane, chloroform, pyridine and ethyl acetate. The fluorescence quenching behaviour was investigated using 1,4-benzoquinone and potassium iodide as quenchers. The photophysical (fluorescence quantum yields and lifetimes) and photochemical (singlet oxygen and photodegradation quantum yields) properties of these novel phthalocyanines (6a-9a and 6b-9b) were studied in DMF. They produced high singlet oxygen (for example phi(Delta) = 0.99 for 7b) and showed appropriate photodegradation (in the order of 10(-5)) which is very important for photodynamic therapy (PDT), and thus these phthalocyanines can be used as Type II photosensitizers in PDT applications.
Keywords: ZINC PHTHALOCYANINE